The Effect Of Member Savings On Profitability In Nahdlatul Ulama Muamalat Cooperative, Kasomalang District, Subang - Solihah, Pini Siti; Andrianasari, Ravita Eka; Romdoni, Indi Auliya (Pascasarjana Universitas Pasundan, 2024)
The Muamalat Nahdlatul Ulama Koperasi is an institution that seeks to increase the economic activities of small entrepreneurs based on sharia principles by managing from the ummah by the ummah and for the ummah. Profitability is an indicator of assessing the good or bad performance in carrying out business activities to get optimal profits. Profitability in a cooperative is influenced by the savings of its members. Members' cooperativedeposits are then used as capital for the cooperative business so as to generate profits. Through the interview method and questionnaire for 71 respondents, the aim was to find out whether or not there was an influence of member savings on profitability in the Muamalat Nahdlatul Ulama Koperasi Kasomalang Subang, The result is that members savings have an effect on profitability. Cooperatives need to increase the recruitment of members throughout the cooperative environment so that member savings have a significant influence on profitability.